Multimedia retrieval - Blanken Henk M; Blok Henk Ernst; De Vries Arjen P; Feng Ling (Berlin Springer-Verlag, 2007)
The single chapters of this books explain the general architecture of multimedia information retrieval systems, various metadata languages like Dublin Core, RDF or MPEG, pattern recognition through Markov models, unsupervised learning, and pattern cluste
Keywords: Database searching; Information retrieval; Multimedia systems